Pengaruh Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Fikih Di MTs Alwashiliyah Perdagangan - Siti Nur Zana; Arifmiboy Arifmiboy; Salmi Wati; Muhiddinur Kamal (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research aims to evaluate the influence of the Contextual Teaching and Learning (CTL) learning model on learning outcomes in the Fiqh subject at MTs Al-Washiliyah Commerce. The research background includes a mismatch between the learning models used by teachers and students' learning needs, low intelligence levels, low learning motivation, irregular study habits, lack of parental attention to children's education, and the influence of the social environment. This research uses a quantitative research design with the approach "The Static Group Comparison: Randomized Control-Group Only Design." The sample was selected based on the students' UTS test results in the Jurisprudence subject. Previously, student learning outcome data was collected to test the normality and homogeneity of data distribution using the Liliefors test. The research results show that the application of the Contextual Teaching and Learning (CTL) learning model has a significant influence on Fiqh learning outcomes. The significance value (Sig.) for the experimental class is 0.000, which is smaller than the research alpha significance level of 0.05. The results of the analysis also show significant differences in Fiqh learning outcomes between the use of the CTL model and the conventional model. Previously, the average pretest score was 74.73, while after implementing the CTL model, the average posttest score increased to 79.33. Thus, this research concludes that the use of the Contextual Teaching and Learning (CTL) learning model is more effective than the direct learning model in improving learning outcomes in Fiqh subjects at MTs Al-Washiliyah Commerce, especially in class VIII.